What drives DS30 Index amid bourse lockdown decision? An emerging economy perspective - Faruq, Mohammad Omar (International Journal of Scientific Research and Management (IJSRM), 2021)
This study measures the impact of the COVID-19 pandemic outbreak on the stock market of Bangladesh amid bourse lockdowns. The top 30 blue-chip companies listed in the DS30 Index of the Dhaka Stock Exchange are used as the sample for this study. Panel data regression analysis has been used after performing several diagnostics tests to assess the impact for January to December during the year 2020. The regression model used in the study considers three key aspects, namely COVID-19, firm-specific factors, and macroeconomic variables amid the bourse lockdown. This study finds that daily trend in affected cases, death cases and investors' attention significantly affect the stock market but does not show any negative relation to conclude. The Government imposed lockdown shows a negative relation with the stock market significantly. Firm-specific variables like daily market capitalization and book to market ratio show a significant negative relationship with the stock market. On the other hand, macroeconomic factors have a significantly positive impact on the stock market amid bourse lockdowns. This study assesses the performance of the Bangladesh stock market by use of DS30 Index listed firms during the COVID-19 pandemic in response to the Government imposed bourse lockdown. This study provides unique insights into how the Bangladesh stock market reacted during the pandemic, along with a rare bourse lockdown decision.